ECONOMIC IMPACT OF IMPLEMENTING DIGITAL MANAGEMENT SYSTEMS ON INNOVATIVE DEVELOPMENT PROCESSES IN ENTERPRISES (American Journal of Business Management, Economics and Banking, 2026)
This article examines the economic impact of implementing Digital Management systems on the innovative development processes of enterprises. The rapid advancement of Industry 4.0 technologies, including artificial intelligence, Big Data, and cloud computing, is reshaping modern management mechanisms and transforming business operations worldwide. Based on the scientific views of both foreign and domestic scholars, the study analyzes the influence of digital management systems on enterprises' innovation activity, labor productivity, and competitiveness. The findings indicate that the implementation of digital management systems contributes significantly to enhancing the level of innovative development, reducing operational costs, and creating new market opportunities for enterprises. Furthermore, the article proposes scientific and practical recommendations aimed at improving digital management practices and accelerating innovative growth in business organizations.